Perception of Society toward Populist Economic Policy for Development Economic: Empirical Research in East Java - Subroto, Waspodo Tjipto; Riyanto, Yatim; Roesminingsih, Maria Veronika; Sukartiningsih, Wahyu (International Journal of Economics and Financial Issues, 2017)
This article is a research study on people given by 480 respondents from the society of East Java, to describe show perception of society about populist economic policy. This study investigates the perception of society toward the role of populist economic policy can be use to foster economic development. Furthermore this study was applied to 480 respondents, who attended in the East of Java. The obtained data from the questionnaires are analyzed through Statistical Package for Social Sciences for Windows 21.0. The resulted from this study if society have positive perception toward populist economics policy for increasing economic development. During the pre survey period about conducting the survey, it was perception from society is the first important to foster economic development. However, results of the survey indicate that perception of society about populist economics policy very contributed to increasing economic development, comparing with the liberalism economics system or socialism economics system. Keywords: Populist Economics, Policy Economics, Development Economics JEL Classifications: F6, P